Terrestrial impact structures as geoheritage: an assessment method of their scientific value and its application to Brazil - Sánchez, Joana Paula (2017)
Terrestrial impact structures are geological and geomorphological features with particular importance to understand the history and evolution of the planet. Impact structures are scattered around the world but in many countries these features are under threat, essentially due to anthropic factors. Impact structures with higher scienti c value should be considered as geological heritage and, consequently, be subjected to geoconservation strategies. In order to select the most important impact structures to be properly conserved and managed, this paper proposes a quantitative assessment method of the scienti c value of these structures. The eight Brazilian impact structures were used to test this method that has the potential to be applied to any geological context in any country. The structures known as Araguainha Dome-MT and Serra da Cangalha-TO reached a higher scienti c value, which justi es the need to develop geoconservation strategies and a proper management.